Evaluation of In vivo antimalarial property of Nyctanthes arbor-tristis (night jasmine) leaves - Lopamudra Das (Wolters Kluwer Medknow Publications, 2021)
Background: Nyctanthes arbor-tristis (NAT) is an ornamental garden plant traditionally used for treating many diseases such as helminthiasis, arthritis, and malaria. Aims: The aim of this study was to validate the ethnobotanical uses of the antimalarial activity of leaves of NAT by in vivo tests. Materials and Methods: Leaves of NAT were identified and authenticated and phytoconstituents of NAT were identified. The antimalarial activity of NAT was studied in in vivo for its schizonticidal activity, repository activity, and curative tests in Swiss albino mice by using Plasmodium berghei (ANKA). Statistical Analysis Used: One-way ANOVA was done for comparison of different groups followed by post hoc analysis (Tukey-Kramer multiple comparison tests). Level of significance was at P < 0.05. Results: The mean schizonticidal activity of NAT increased from 14.21 to 46.15 (P < 0.01) with doses ranging from 100 to 200 mg/kg compared to 67.29 with that of chloroquine (CQ). The repository activity with NAT doses 100–200 mg/kg increased from 12.91 to 42.85 (P < 0.01) compared to 78.79 in pyrimethamine 1.2 mg/kg/day. In Rane's test, there was chemosuppression in range of 55.50–65.02 (P < 0.01) with NAT in doses of 100–200 mg/kg compared to 74.15 with that of CQ 5 mg/kg. Conclusions: The antiplasmodial activity of NAT might be like that of artemisinin by producing oxidative stress mostly due to the iridoid glycosides. The active phytoconstituent(s) responsible may be tested individually or in combination both by in vitro and in vivo studies to identify the active chemical ingredient.